THE EFFECT OF SOLID LIPID NANOPARTICLES ON TAMOXIFEN-RESISTANT BREAST CANCER CELLS - Eskiler, Gamze Guney; Cecener, Gulsah; Dikmen, Gokhan; Genc, Lutfi; Egeli, Unal (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
To overcome the acquired Tamoxifen (Tam) resistance in Tam-resistant breast cancer cells without damaging normal cells, we have examined the therapeutic efficacy of Tam-loaded solid lipid nanoparticles (SLNs). Tam-loaded SLNs were produced by hot homogenization method. After characterization, in vitro cytotoxic and apoptotic activity of Tam-SLNs were evaluated in MCF7, MCF7-TamR (Tam-resistant breast cancer cells) and MCF10A cells. Tam-SLNs had an average size nearly 300 nm and a zeta potential of approximately-40 mV. In vitro cytotoxicity results showed that Tam-SLNs indicated the cytotoxic and apoptotic activity on MCF7 and MCF7-TamR cells. We found that MCF7-TamR cell viability was also suppressed significantly by Tam-SLNs and thus, Tam-SLNs could delay and overcome Tam-resistance (p<0.05). Furthermore, the Tam-SLNs did not induce apoptosis on MCF10A control cells. The lowest MCF10A cell viability was 83.0% whereas MCF7 and MCF7-TamR (R↔ and R↑) cells viability are reduced to 21.98%, 27.5% and 29.4% at 10 µM of Tam-SLNs, respectively (p<0.05). The obtained results were supported by apoptosis assays. SLNs-delivery system provided therapeutic efficacy to overcome Tam-resistance thanks to unique features of SLNs including small size, drug accumulation in the tumor site and controlled drug release. Therefore, Tam-SLNs may have therapeutic potential for the treatment of TAM-resistant breast cancer.